Scientific management of insect infestation during storage of minor millets - P N, GURU; Balakrishnan, Renu; Nancy (Indian Farming, 2023)
On the occasion of International Year of Millets 2023, the nutri-cereals/ minor millets are getting special attention in diet. Previously the production was limited for these crops due to several reasons, however the nutritional benefits and the hardy adaptation made these crops popular day-by-day. Apart from production, the storage of these grains also needs to be taken care. Insects are the major culprits of the storage losses of millets. Management of these grains for their safer storage is the need of hour. This article provides the list of important insects infesting millets during storage and their scientific management to minimise the losses.